(3JMbjb CLhHI deSGFd eNJdaIs - (3cGXe Hf Ydjs ((3CMeO Hf Rjf GdOjf s)
(3ChdgG (B:s
(3hHYO CfRd Hg GdeGA Ydi GdCQV GdLQa CMbQ YHGO Gddg GdYHO GdeScjf cGXe Hf Ydi HJMbjb CLhHI eSGFd KdGK s
(3BNQgG (B:s
(3aGYde Cf dfG ai HYV GdCMhGd EWdGbGJ dHYV ai SjGb cdGefG aJOHQhG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs